Determination of Susceptibility of Bacterial Infections to Antibiotics and Prevention of Nosocomial Infections - Raxmonova Iroda Odilovna (International Journal on Human-Computing Studies, 2023)
In this article describe the definition of sensitivity of microorganisms to anti-bacteriology equipments has big values at treatment of infectious diseases and preventive maintenance in infection sick-lists. The results bacteriological rezistogramm at epidemiological research is the basic marker. Keywords: disk-diffuse, F- plasmid, L-forma, S-forma, MIK, MBK.